The Wavelet Method for the Analysis of Electron-Transfer Kinetics in Bacterial Reaction Centres - Barabash, Yu.M.; Zabolotny, M.A.; Serdenko, T.V. (Наносистеми, наноматеріали, нанотехнології, 2010)
In a given paper, kinetics of electron transfer in bacterial reactive centres (RC) is discussed. Aspects of relaxation processes and photoinduced structural changes in a molecular complex RC of Rhodobacter sphaeroides as a result of intramolecular electron transfer are studied by the wavelet analysis. Relaxation kinetics has S-shaped character of the time-dependence of a constant of rate of electron return from an acceptor after turning off stimulating light. Relaxation curves of RC are non-stationary (time-dependent). Twolevel model of electron transfer is considered. Reaction centres are regarded as dynamic in time and identical with each other. Wavelet analysis of relaxation kinetics allows us to assume that exponents of relaxation curves are not involved simultaneously, but appear by turns. В данной работе обсуждается кинетика переноса электронов в бактериальных реактивных центрах (РЦ). Аспекты релаксационных процессов и фотоиндуцированных структурных изменений в молекулярном комплексе РЦ Rhodobacter sphaeroides как результат внутримолекулярного переноса электронов были изучены при помощи вейвлет-анализа. Релаксационная кинетика имеет S-образный характер зависимости от времени константы скорости возврата электрона от акцептора после выключения стимулирующего света. Релаксационные кривые RC являются нестационарными (зависят от времени). Рассмотрена двухуровневая модель переноса электронов. Центры реакции рассматриваются как динамические во времени и идентичные друг другу. Вейвлет- анализ кинетики релаксации позволяет предположить, что экспоненты релаксационных кривых не включаются одновременно, а появляются поочередно. У даній роботі обговорюється кінетика переносу електронів у бактеріяльних реактивних центрах (РЦ). Аспекти релаксаційних процесів і фотоіндукованих структурних перетворень у молекулярному комплексі РЦ Rhodobacter sphaeroides як результат внутрішньомолекулярного переносу електронів було вивчено вейвлет-аналізою. Релаксаційна кінетика має S-подібний характер залежности від часу константи швидкости повернення електрона від акцептора після вимикання стимулювального світла. Релаксаційні криві РЦ є нестаціонарними (залежать від часу). Розглянуто дворівневий модель переносу електронів. Центри реакції розглянуто як динамічні у часі й ідентичні один до одного. Вейвлет-аналіза кінетики
релаксації дозволяє припустити, що експоненти релаксаційних кривих не включаються одночасно, а з’являються по черзі.